A study of some weeds of Pakistan and their response to abiotic stress - a review - Shumail, Hoor; Khalid, Shah; Ghaffar, Nasreen; Inzimam Ul Haq, Syed (Journal of Pure and Applied Agriculture, 2023)
Weeds are invasive plants that compete the crops and native plant species for space, moisture, and available nutrients in the environment. Weeds are subjected to a variety of biotic and abiotic stresses. Abiotic stresses are inevitable and have resulted in extremely harmful factors influencing weed and crop plants growth and development. Abiotic stresses such as drought, salinity, and temperature fluctuations cause weeds to undergo a variety of anatomical, physiological, morphological, biochemical, and genetic changes as a response to harsh environmental conditions. To cope with these abiotic stress conditions, various weeds employ various strategies such as the production of heat shock proteins, activation of stress genes, antioxidant stress mechanisms, increases or decreases in amino acid metabolism, decreased photosynthesis, membrane leakage, production of super oxides, and so on. In this review article we have mainly focused on the ten most important and aggressive weeds i.e Cynodon dactylon (L.) Pers., Phalaris minor Retz., Desmostachya bipinnata (L.) Stapf, Sorghum halepense (L.) Pers., Echinochloa colona L., Cannabis sativa L., Imperata cylindrica (L.) P. Beauv., Sonchus oleraceus L., Carthamus oxyacantha M. Bieb, Fimbristylis littoralis Gaudich invading different areas of Pakistan and their response towards abiotic stresses. Although many studies have been conducted to evaluate the morphological, anatomical, physiological, and biochemical response towards abiotic stress in weeds. However, more research into the main mechanisms behind abiotic stress tolerance is still needed. © 2022 Department of Agricultural Sciences, AIOU